Isaac Newton's scientific method turning data into evidence about gravity and cosmology - Harper, William L. (William Leonard), 1943- (Oxford : Oxford University Press, 2011)
Harper presents an account of Isaac Newton's work on gravity and the cosmos. He argues that Newton's inferences from phenomena realize an ideal of empirical success that is richer than prediction, and explores the ways in which Newton's method aims to turn theoretical questions into ones which can be answered empirically.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Newton, Isaac, -- 1642-1727.; Gravitation; Gravity; Cosmology